A nanoporous metal phosphide catalyst for bifunctional water splitting. Issue 14 (14th March 2018) - Xu, Wence; Zhu, Shengli; Liang, Yanqin; Cui, Zhenduo; Yang, Xianjin; Inoue, Akihisa
Abstract : Nanoporous Ni–Fe–P prepared by dealloying exhibits excellent bifunctional catalytic activity for HER and OER under alkaline conditions. Abstract : The development of high-performance earth-abundant bifunctional electrocatalysts for both the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is highly desirable, but remains a significant challenge. Herein, a type of content-controllable amorphous Ni–Fe–P catalyst with a bicontinuous nanostructure has been reported to be useful as a bifunctional electrocatalyst for overall water splitting. np-(Ni x Fe1− x )4 P5 is prepared simply by an electrochemical dealloying method. Owing to the bicontinuous nanostructure, amorphous atomic arrangement, metallic nature, and the substitution of Ni by Fe, np-(Ni0.67 Fe0.33 )4 P5 exhibits excellent catalytic performance with the overpotentials of 245 mV and 120 mV at the current density of 10 mA cm −2 for OER and HER in 1 M KOH, respectively. Furthermore, the np-(Ni0.67 Fe0.33 )4 P5 catalyst as both an anode and a cathode shows a high current density of 10 mA cm −2 at a low potential of 1.62 V in a two-electrode water electrolysis system with excellent stability for 20 h.